LiebeLesen. Potsdamer Vorlesungen zu einem großen Gefühl und dessen Aneignung - Ette, Ottmar (AULA, 2020)
The lecture volume plumbs a seductively diverse and infinitely confusing subject: love. From Tristan and Isolde to Don Juan, Cecilia Valdes, Emma Bovary, and the love fables of modern mass media, the relationship between love and life, and between literature and passion, is analyzed in this volume with scholarly dispassion.